Analisis Teknikal Return Saham dengan Indikator-Indikator Bollinger Band, Parabolic SAR, dan Stochastic Oscillator - Muis, Ikhza Syafa; Prajawati, Maretha Ika; S, Basir (Jurnal Samudra Ekonomi dan Bisnis, 2021)
In making a decision to buy shares in the stock market, an investor must know the analytical methods involved in stock investing. One of the methods used is technical analysis. This study aims to determine the comparison of stock returns generated using the Bollinger Band, Parabolic SAR, and Stochastic Oscillator indicators. This type of research is a quantitative approach with a comparative method. The sampling technique used purposive sampling, in order to obtain 14 companies. The results show that the indicators of Bollinger Band, Parabolic SAR, and Stochastic Oscillator can be used as guidelines in determining the buying and selling of stocks to get optimal returns.